2020
DOI: 10.21203/rs.3.rs-20601/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-Term Trajectories of BMI Predict Carotid Stiffness and Plaque Volume in Type 2 Diabetes Older Adults: a Cohort Study.

Abstract: Background: High body mass index (BMI) is a risk factor for type 2 diabetes and cardiovascular disease. However, its relationships with indices of carotid stiffness and plaque volume are unclear. We investigated associations of long-term measurements of BMI with indices of carotid stiffness and atherosclerosis among non-demented diabetes patients from the Israel Diabetes and Cognitive Decline (IDCD) study. Methods: Carotid ultrasound indices [carotid intima media thickness (cIMT), distensibility, elastography … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
2
1
0
Order By: Relevance
“…A higher BMI was significantly associated with the risk of CAS, which was similar to previous studies [21,22]. A cohort study found that obesity is associated with the carotid atherosclerosis index and plaque volume in older adults with type 2 diabetes [22]. Both ex-smokers and current smokers had an increased risk of CAS in our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A higher BMI was significantly associated with the risk of CAS, which was similar to previous studies [21,22]. A cohort study found that obesity is associated with the carotid atherosclerosis index and plaque volume in older adults with type 2 diabetes [22]. Both ex-smokers and current smokers had an increased risk of CAS in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Increasing attention is being paid to the importance of lifestyle factors in the prevention of atherosclerosis [20]. A higher BMI was significantly associated with the risk of CAS, which was similar to previous studies [21,22]. A cohort study found that obesity is associated with the carotid atherosclerosis index and plaque volume in older adults with type 2 diabetes [22].…”
Section: Discussionsupporting
confidence: 80%
“…Carotid tensile stress is related to its elasticity, 23 and Claudio et al 24 found that Carotid endothelial shear stress reduction is an independent predictor of atherosclerosis. In addition, in a previous study, 25 increased TG levels and decreased HDL‐C levels were related to arteriosclerosis. Further, adipose tissue‐derived inflammatory factors—resistin, vaspin, and visfatin—were associated with the pathogenesis of carotid atherosclerosis, including initial activation of endothelial cells.…”
Section: Discussionmentioning
confidence: 71%